The posture effects on trumpet playing (sitting and standing) / Muhammad Aiman Churayme - Churayme, Muhammad Aiman (Faculty of Music, 2012)
This study was conduct to examine the effects of posture on trumpet playing while sitting and standing. The purpose of this study is to find out the effects of posture on trumpet playing while sitting and standing. For this particular study, the data are collected from books, article and journal by different authors who talk about posture. The data gathered was analyzed and will conclude based on the three research question. From the findings of this study, posture directly can effects a trumpet player performance and the player should determined on an individual basis based on the comfortability each player or performer.